2012
DOI: 10.4271/2012-01-1868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controlled Modulation on Surface Textures in Deep-Hole Drilling

Abstract: Recently, a new technology, called Modulation-Assisted Machining (MAM), has been adopted in commercial deephole drilling processes, including gun-drilling applications [2]. In MAM a low-frequency, controlled oscillation is superimposed on the drilling process to alter the mechanics of chip formation [3,4,5,6]. ABSTRACTDeep-hole drilling is among the most critical precision machining processes for production of high-performance discrete components. The effects of drilling with superimposed, controlled low-frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Of greater concern is the generation of severe cracks propagating approximately parallel to the feed direction when turning, which was observed even when employing 'gentle' operating parameters (10-40 m/min cutting speed, 0.05-0.35 mm/rev feed rate, 0.05-0.7 mm depth of cut), see Fig. 18a [139,195]. Klocke et al [112] suggested that it was possible to obtain crack free surfaces when turning g-TiAl by increasing the cutting speed ( 100 m/min) in order to improve workpiece ductility (Fig.…”
Section: Ti-based Superalloysmentioning
confidence: 97%
See 2 more Smart Citations
“…Of greater concern is the generation of severe cracks propagating approximately parallel to the feed direction when turning, which was observed even when employing 'gentle' operating parameters (10-40 m/min cutting speed, 0.05-0.35 mm/rev feed rate, 0.05-0.7 mm depth of cut), see Fig. 18a [139,195]. Klocke et al [112] suggested that it was possible to obtain crack free surfaces when turning g-TiAl by increasing the cutting speed ( 100 m/min) in order to improve workpiece ductility (Fig.…”
Section: Ti-based Superalloysmentioning
confidence: 97%
“…An illustration of enhanced chip control and surface finish obtained when applying MAM in deep hole gun drilling of Ti-6A-l4V is shown in Fig. 35 [139].…”
Section: Vibration-assisted Machiningmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies established that low-frequency vibration drilling could divide the chips and reduce the thrust force and torque (Toews et al, 1998). Furthermore, it was shown that the accuracy of the inner surface of the hole was improved by low-frequency vibration drilling in deep-hole processing (Mann et al, 2013). Low-frequency vibration drilling can also extend tool life (Arai et al, 1989;Jin and Murakawa, 2000;Nanbu et al, 2012;Sugihara and Enomoto, 2016) with the same drilling times as conventional drilling.…”
Section: Introductionmentioning
confidence: 91%
“…As reported by Mann et al [8], the micro-holes with aspect ratio of 44 are processed by drilling. Das et al [9] reported that the micro-holes with 200 μm∼ diameter are obtained on 304 stainless steel sheets with 60 μm thickness by electrochemical machining, Thanigaivelan et al [10] obtained micro-holes by using this method on copper, and Qu et al [11] also fabricated micro through-holes by electrochemical machining on polydimethylsiloxane (PDMS).…”
Section: Introductionmentioning
confidence: 99%